Diagnostic Laparoscopy with Ultrasound Still Has a Role in the Staging of Pancreatic Cancer: A Systematic Review of the Literature. (30th March 2016) - Levy, Jordan; Tahiri, Mehdi; Vanounou, Tsafrir; Maimon, Geva; Bergman, Simon
Abstract : Background . The reported incidence of noncurative laparotomies for pancreatic cancer using standard imaging (SI) techniques for staging remains high. The objectives of this study are to determine the diagnostic accuracy of diagnostic laparoscopy with ultrasound (DLUS) in assessing resectability of pancreatic tumors. Study Design . We systematically searched the literature for prospective studies investigating the accuracy of DLUS in determining resectability of pancreatic tumors. Results . 104 studies were initially identified and 19 prospective studies (1, 573 patients) were included. DLUS correctly predicted resectability in 79% compared to 55% for SI. DLUS prevented noncurative laparotomies in 33%. Of those, the most frequent DLUS findings precluding resection were liver metastases, vascular involvement, and peritoneal metastases. DLUS had a morbidity rate of 0.8% with no mortalities. DLUS remained superior to SI when analyzing studies published only in the last five years (100% versus 81%), enrolling patients after the year 2000 (74% versus 58%), or comparing DLUS to modern multidimensional CT (100% versus 78%). Conclusion . DLUS seems to still have a role in the preoperative staging of pancreatic cancer. With its ability to detect liver metastases, vascular involvement, and peritoneal metastases, the use of DLUS leads to less noncurative laparotomies.